Foregribelsens dialektik: ”skolens” nærvær i børnehavens pædagogiske værdiunivers - Bent Olsen (Nordisk Barnehageforskning, 2015)
Abstract: The article presents a study of some 700 day-care staff member’s attitudes towards children’s transition from kindergarten to a coming life as pupils in the school system. The transition is studied as rites of passage and as ascesis along the concept of Bildung. In addition findings are also analyzed along the value horizon of autonomy and conformity. The theoretical approach is based on the framework developed by Pierre Bourdieu, and the Grid Group Cultural Theory of Mary Douglas. The empirical part consists of answers to a questionnaire from some 700 staff members of 80 kindergartens in two Danish municipalities. The conclusions points to a high potential of conformist values and points to the long ignored ascetic dimension of Bildung as a central issue in the educational efforts of transition.